Analysis of Wi-Fi Network Usage with Cellular Data Packages on Video Call Service Quality - Arya darma wijaya, Arya; Elvin Andrean Theranata; Yustian Servanda, A.Md, S.Kom, M.Kom (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Abstract Video calls have now become an important part of daily activities, from personal communication to work meetings and online learning. However, the quality of video calls is highly dependent on the internet network used. This study aims to analyze the comparison of the quality of video call services when using Wi-Fi networks and cellular data packet networks. Testing was carried out by utilizing several main parameters of network quality, such as data transfer speed (throughput), data packet loss, delay, and signal interference (jitter). In addition, signal quality was also analyzed using the SINPO (Signal, Interference, Noise, Propagation, Overall) parameters, and signal strength was measured using the GNetTrack application. Testing was carried out using the Telegram video call application at three different times—morning, afternoon, and evening—for three consecutive days. The results of the study showed that the quality of video call services with Wi-Fi networks tends to be more stable and consistent compared to cellular data packets, especially during times of heavy internet usage. However, in conditions of a strong cellular signal, the quality of video call services can match or even approach the quality of Wi-Fi. This study concludes that network type and usage time have a significant impact on video call quality, and it is important for users to choose a network that suits environmental conditions and communication needs. Keywords: Video call, Wi-Fi, Mobile data, Network quality, SINPO, QoS